The Cult of Saints among Muslims and Jews in Medieval Syria: By Josef Meri (Oxford: Oxford University Press, 2002. 327 pages.) (American Journal of Islam and Society, 2004)
Contemporary Jewish-Muslim relations are so mired in the Middle East’spolitical conflict that most people are often quite surprised to learn of theremarkable theological, legal, and mystical intersections between both traditions.Modern political hostilities centered on the Palestinian-Israelidivide have almost entirely clouded the shared Semitic heritage of faithsthat were, until just a little more than 50 years ago, invariably stamped bythe Christian West with the seal of “otherness” – an “internal otherness” inthe case of Judaism, and an “external otherness” in the case of Islam.In this light, Josef Meri’s work is a welcome contribution to the scholarlystudy of Jewish-Muslim relations. The study raises our awareness of both religions’ common cultural and intellectual history: more specifically,to the medieval Muslim and Jewish pilgrimage culture of saint venerationin Syria, and, to a lesser extent, other regions of the Near East. The workgrew out of the author’s doctoral dissertation at Oxford, done under thesupervision of Wilferd Madelung and Daniel Frank, and bears the mark ofthe many hours Meri must have spent as a scholarly archeologist diggingthrough an enormous range of classical Arabic and Hebrew texts as well aspertinent secondary literature.Although the concentration of the comparative analysis tilts toward theIslamic side (the author notes that the evidence for Jewish saint venerationis considerably less), he still manages to explore the parallel concepts, religiouspractices, and architectural facets relevant to his analysis with reasonablesuccess. The work is not simply a descriptive account of Jewishand Muslim saint veneration, but an assessment of the psychological andcultural modes that accompany such forms of religious expression. To thisend, Meri draws out some of the wider theoretical issues pertaining to theconstruction of sacred space and the social function of saints and pilgrimagesites ...